Alumoxane Film for Corrosion Protection of 2024 Aluminum Alloy - Paez-Collio, M; Paez-Collio, M (Elsevier Editora Ltda, 2023)
Alumoxane film on anodized 2024 was obtained using stearic acid to prevent corrosion in a chloride medium. A cleaning pretreatment was applied to the metal surface to improve the adhesion and formation of the alumoxane film using three different sprays, ethanol, water, and NaOH. Then a molten stearic acid was applied to form an alumoxane. The obtained films were characterized by X-ray photoelectron spectroscopy and glow discharge optical emission spectroscopy, and electrochemical techniques, such as linear sweep voltammetry and electrochemical impedance spectroscopy, evaluated the corrosion protection. The surface analyses suggested an interaction between the boehmite and stearic acid to form alumoxane, and the electrochemical results revealed that alumoxane film using ethanol significantly improved the protection against corrosion due to the formation of compact and homogeneous films with a hydrophobic characteristic for the 2024-T3 alloy. © 2023 The Author(s)